Festival Budaya Sebagai Media Bank Indonesia Dalam Mempromosikan Uang Elektronik (e-money) di Masyarakat: Cultural Festival as Bank Indonesia Media in Promoting Electronic Money (e-money) in the Community - Jeby Fahira; Muhammad Iqbal Fasa; Suharto (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2023)
Basically society has experienced significant technological developments. One of them is the existence of online transactions in the form of e-money. According to the Indonesian Banking Regulation Number: 12 November 2009 PBI Regarding Electronic Money Electronic Money. Electronic money is issued based on the value of money previously deposited by the holder to the issuer that is stored electronically in media such as servers or chips, with the money not as deposits, and used as payments. The promotional technique carried out by BI is by holding a begawi festival which is complemented by the presence of MSMEs who participate to provide socialization of payments via e-money in the community. The research method used is qualitative method. The purpose of this study is to find out how the promotion strategy is carried out by Bank Indonesia Kpw Lampung regarding e-money transactions. In addition, the purpose of this study is to find out payment applications such as OVO, GO-PAY, and Dana used in e-money transactions.